Association of health behaviors with healthcare workers’ physical and psychological well-being: Learning from the COVID-19 pandemic - Elie Mulhem; Lori Lackman Zeman; Karen Childers; Sujoy Roy; Ramin Homayouni (PLoS ONE, 2025)
Background During the COVID-19 pandemic healthcare workers reported using a variety of positive or negative health behaviors as a strategy to cope with the increased stress at work and home. This study examined the extent of healthcare workers’ engagement in various health behaviors and the association of these behaviors with changes in self-reported physical and psychological well-being during the pandemic. Methods A survey was developed and administered to healthcare workers in a large healthcare system in Southeast Michigan between November 2, 2020, and January 21, 2021, during Michigan’s second COVID-19 surge. Results During the study period 368 healthcare workers completed the survey. The majority of participants were female (83.2%) and aged between 25−34 years (29.3%). Most participants reported a drop in their psychological well-being and physical health during the pandemic. Overall, 14.8% to 47.7% of participants rated their engagement in a positive health behavior as “often” or “very often”. Engagement in most positive health behaviors was associated with higher self-rating of physical health and psychological well-being. The estimated decrease in psychological well-being scores for participants who often/very often engaged in pleasurable activities was 0.91 points less (p = 0.003, 95% CI [−1.50, −0.32]) than for those who rarely/never engaged in such activity. Exercise , healthy eating , getting enough sleep , engaging in pleasurable activities , focusing on gratitude and positive things , and getting social support appeared to positively influence the degree to which participant’s physical health declined. After controlling for age, gender and other potential confounders, each additional positive health behavior was associated with a 0.22-point decrease in the rate of decline in overall physical health (p = 0.000, 95% CI −0.35, −0.10). Discussion Healthcare workers who regularly engaged in positive health behaviors during the pandemic reported better psychological and physically well-being than those who did not before and during COVID-19. Engaging in pleasurable activities was the only health behavior in our study that demonstrated a potential protective effect against the decline in psychological well-being during the pandemic. Several other positive health behaviors were associated with a lower rate of decline of physical health during the pandemic. Health systems should consider implementing strategies to increase opportunities for pleasurable activities for healthcare workers, both in the workplace and at home, especially during times of increased stress.